TMIC-01. THE DYSTROGLYCAN RECEPTOR MAINTAINS GLIOMA STEM CELLS IN THE VASCULAR NICHE. (11th November 2019) - Day, Bryan; Lathia, Justin; Bruce, Zara; Ensbey, Kathleen; Chieh Lim, Yi; Jamieson, Paul; D'Souza, Rochelle; Akgul, Seckin; Offenhauser, Carolin; Baumgartner, Ulrich; Smith, Fiona; Li, Yuchen; et al.
Abstract: Glioblastomas (GBMs) are malignant central nervous system (CNS) neoplasms with a very poor prognosis. They display cellular hierarchies containing self-renewing tumourigenic glioma stem cells (GSCs) in a complex heterogeneous microenvironment. One proposed GSC niche is the extracellular matrix (ECM)-rich perivascular bed of the tumour. Here, we report that the ECM binding alpha (α) subunit of the dystroglycan (DG) receptor is expressed and functionally glycosylated on GSCs residing in the vascular niche. Glycosylated αDG is also expressed highly on the most aggressive mesenchymal-like GBM tumour tissue. Furthermore, we found that DG acts to maintain a de-differentiated stem cell-like phenotype via tight control of MAPK activation. Antibody-based blockade of αDG induces robust ERK-mediated differentiation leading to reduced GSC potential. DG was shown to be required for tumour initiation, with constitutive loss significantly delaying or preventing tumourigenic potential in-vivo . These findings reveal a central role of the DG receptor not only as a structural element but also as a critical factor in the maintenance of GSCs in the GBM vascular niche.